Loss of Fibrinogen in Zebrafish Results in Symptoms Consistent with Human Hypofibrinogenemia - Vo, Andy H.; Swaroop, Alok; Liu, Yang; Norris, Zachary G.; Shavit, Jordan A. (PLOS ONE, 2013)
Cessation of bleeding after trauma is a necessary evolutionary vertebrate adaption for survival. One of the major pathways regulating response to hemorrhage is the coagulation cascade, which ends with the cleavage of fibrinogen to form a stable clot. Patients with low or absent fibrinogen are at risk for bleeding. While much detailed information is known about fibrinogen regulation and function through studies of humans and mammalian models, bleeding risk in patients cannot always be accurately predicted purely based on fibrinogen levels, suggesting an influence of modifying factors and a need for additional genetic models. The zebrafish has orthologs to the three components of fibrinogen (fga, fgb, and fgg), but it hasn’t yet been shown that zebrafish fibrinogen functions to prevent bleeding in vivo. Here we show that zebrafish fibrinogen is incorporated into an induced thrombus, and deficiency results in hemorrhage. An Fgb-eGFP fusion protein is incorporated into a developing thrombus induced by laser injury, but causes bleeding in adult transgenic fish. Antisense morpholino knockdown results in intracranial and intramuscular hemorrhage at 3 days post fertilization. The observed phenotypes are consistent with symptoms exhibited by patients with hypo- and afibrinogenemia. These data demonstrate that zebrafish possess highly conserved orthologs of the fibrinogen chains, which function similarly to mammals through the formation of a fibrin clot.